Mental maps and Canada's post-war Asian policy. (December 2020) - Webster, David
This article takes up the concept of mental maps as lens through which to survey Canada–Asia relations. Before Canadians could embrace Asia politically and economically, they had to stop imagining Asia as culturally distant. Their mental maps—the way they imagined the world—formed the invisible background to policy-making. Through an engagement with Greg Donaghy's work on Canadian relations with Asia, this article makes the case for using mental maps to understand trans-Pacific relations.